A case of penetration and migration of a fishbone through the floor of the mouth to the anterior cervical region - SHIMIZU, Mikio; HAYASHI, Houka; YASUI, Akio; KATO, Mugio; YATA, Hiroaki; OTANI, Eiji (Japanese Journal of Oral and Maxillofacial Surgery, 2001)
We report a rare case of migration of a fishbone. The patient was a 56-year-old woman who had swallowing and pharyngeal pain when eating. Radiographic and computed tomographic examinations showed a foreign body in the floor of the mouth. An intraoral attempt at removal was unsuccessful. Nine days later, the fishbone had penetrated the floor of the mouth, passed through the hyoid bone, and migrated to the anterior cervical region. The foreign body was surgically removed and was found to be a fishbone.